Profound Cardiac Sympathetic Denervation Occurs in Parkinson Disease - Amino, Takeshi (Brain Pathol, 2006)
In the last few years, cardiac sympathetic dysfunction in Parkinson disease (PD) has been postulated on the basis of decreased cardiac uptake of sympathoneural imaging tracers. However, the pathological substrate for the dysfunction remains to be established. We examined the left ventricular anterior wall from postmortem specimens with immunohistochemical staining for tyrosine hydroxylase (TH), neurofilament (NF) and S‐100 protein in PD patients and control subjects, and quantified the immunoreactive areas. As TH‐immunoreactive axons nearly disappeared and NF‐immunoreactive axons drastically decreased in number, the morphological degeneration of the cardiac sympathetic nerves in PD was confirmed. Quantitative analysis showed that sympathetic nerves were preferentially involved. Triple immunofluorolabeling for NF, TH, and myelin basic protein showed clearly the profound involvement of sympathetic axons in PD. The extent of involvement of the cardiac sympathetic nerves seems likely to be equivalent to that in the central nervous system, including the nigrostriatal dopaminergic system. PD affects the cardiac sympathetic nervous system profoundly as well as nigrostriatal dopaminergic system.